Potencial uso da Artemisia annua na aquicultura - Soares, Michelly Pereira (Universidade Federal de São Carlos, 2021)
Fish farming in Brazil has shown great growth in recent years, mainly related to the excellent potential of some species grown in intensive production and the great acceptance of these products by the consumer market. The increase and intensification of fish production systems requires high-density cultivation and the adoption of different management technologies, which on the one hand result in excellent production gains, but which, on the other hand, can subject animals to stress demanding greater efficiency of the immune system. With the appearance of different types of diseases, fish farmers increasingly need to use chemotherapy and antibiotics to stem the spread of diseases common to intensified production systems. In addition, antibiotics are used as growth promoters, which generate excellent results, but their use has been increasingly limited for this purpose, as inappropriate or indiscriminate use can have a negative impact on both fish and the environment. In view of this, in recent years, products of natural origin have been studied for their ability to stimulate the immune system and control the main diseases in fish farming. Thus, the objective of this work was to evaluate the use of Artemisia annua, a medicinal plant easily found in Brazil, as an anti-stress agent, immunostimulant, growth promoter, antibacterial and therapeutic. The use of a feed formulation containing supplementation with alcoholic extract of A. annua improves feed conversion, increases growth, improves the immune system and minimizes the stress response of farmed fish, improving resistance to the main bacteria that affect the species. Also, bioactive components of the extract and alcoholic fractions of A. annua have the potential to inhibit growth and eliminate Aeromonas hydrophila, Streptococcus agalactiae and Flavobacterium columnare, and can be applied in the treatment of bacterial infections. The results of this study contribute to the development of bioproducts for use in fish farming, collaborating with the strengthening and consolidation of production, of great economic importance. Therefore, it is hoped with the results generated contribute to the reduction of economic losses due to high mortality rates in fish farming resulting from diseases and to avoid dependence on the use of chemotherapeutic agents and synthetic antibiotics.
Potential use of Artemisia annua in aquaculture
Keywords: Aditivos naturais; Extrato alcoólico; Artemisinina; Bactérias patogênicas de peixes; Imunoestimulantes fitoterápicos; Promotor de crescimento; Natural aditives; Alcohol extract; Artemisinin; Fish pathogenic bactéria; Herbal immunostimulants; Growth promoter; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA::AQUICULTURA::PISCICULTURA; CIENCIAS BIOLOGICAS::FISIOLOGIA